Belize : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
Belize should reduce debt ratios to comfortable levels for smooth market access, and reduce liquidity risks by stabilizing debt service. Streamlined management of the oil fund should be considered. Fiscal measures should compensate for the loss of oil revenues in the budget and avoid new borrowing. This note explores alternative measures of reserves adequacy and concludes that a reserves target of three months of imports is a reasonable benchmark. Reforms enabling more effective liquidity management involve removing the ceilings and moving to market-based interest rates.